Governance and Government Subsidies as Drivers of Financial Performance: A Comparative Study of Three Strategic Indonesian Transportation SOEs (2014–2023) - Nurmala, Nurmala; Haryanto, Haryanto (Universitas Negeri Padang, 2026)
State-owned enterprises (SOEs) play a pivotal role in Indonesia’s transportation system, balancing financial sustainability with social service obligations. Their performance often relies on fiscal intervention and governance quality, raising concerns about the effectiveness of subsidies and oversight mechanisms. This study examines the effects of government subsidies, corporate governance, and board of commissioners’ meetings on the financial performance of three strategic Indonesian transportation SOEs: PT PELNI (Persero), PT ASDP (Persero), and PT KAI (Persero). Multiple linear regression was applied to secondary data from annual reports, using operating revenue, return on assets (ROA), and return on equity (ROE) as performance indicators. The findings show that government subsidies and corporate governance significantly enhance operating revenue, while their impact on profitability remains limited. Subsidies strengthen service capacity but reduce asset efficiency, whereas corporate governance improves accountability and operational consistency. Board meeting frequency has no significant effect, suggesting that effectiveness depends more on meeting quality than quantity. Overall, the financial performance of the examined SOEs is shaped by institutional mechanisms balancing public mandates and commercial objectives. This study integrates agency theory, stakeholder theory, and public economics to explain how fiscal support and governance interact to determine financial outcomes in an emerging economy.